NEWS OBJECTIVITY : A COMPARISON OF ARTICLES ABOUT PILKADA IN WEST JAVA BETWEEN KOMPAS AND REPUBLIKA - Dahlia Agustina, - (2009)
This study entitled "News Objectivity: A Comparison of articles about Pilkada in West Java between Kompas and Republika" aims at revealing objectivity of Kompas and Republika on Pilkada issue and finding out the ideology behind the objectivity. This study employed qualitative method and applied critical discourse analysis as framework. The data was collected by purposive sampling. The data sources were four texts from Kompas and Republika. The study revealed that Kompas tends to stand on Da'i side and Republika tends to stand on Hade side. Republika has religion background, so Republika concerns on conveying of couple with similar background.